(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article highlights the theoretical foundations of linguacultural and its significance in studying the relationship between language and culture. It analyzes the formation process of linguacultural, its main concepts, and the role of the linguacultural category in expressing cultural meaning and national mentality through language units. Furthermore, based on the linguacultural approach, the article reveals the possibilities of identifying cultural codes, phraseological units, and metaphors reflected in the speech of characters in poetic texts.